Mengoptimalkan kejelasan kebutuhan sistem melalui iterasi prototyping: sebuah pendekatan praktis - Mutawali, Qusay (Maliki Interdisciplinary Journal, 2025)
This study examines the effectiveness of an iterative prototyping approach in improving system requirements clarity. Vague requirements specifications are a major challenge in information systems development, often resulting in project failure and stakeholder dissatisfaction. Through an empirical study of 17 software development projects over a 24-month period, this study demonstrates that implementing iterative prototyping cycles significantly improves the precision of system requirements articulation, reduces miscommunication between developers and stakeholders, and facilitates a deeper understanding of functional and non-functional requirements. We introduce the “Continuous Requirements-Oriented Prototyping” (PBBOK) framework that integrates an agile approach with structured stakeholder validation techniques. The results indicate that this approach reduces development time by 28% and increases end-user satisfaction by 32% compared to conventional methodologies. These findings contribute significantly to the understanding of the crucial role of iterative prototyping in improving system requirements clarity and optimizing the software development process.